Guidelines for the management of inflammatory bowel disease in adults. Issue 5 (4th April 2011) - Mowat, Craig; Cole, Andrew; Windsor, Al; Ahmad, Tariq; Arnott, Ian; Driscoll, Richard; Mitton, Sally; Orchard, Tim; Rutter, Matt; Younge, Lisa; Lees, Charlie; Ho, Gwo-tzer; et al.
Abstract : The management of inflammatory bowel disease represents a key component of clinical practice for members of the British Society of Gastroenterology (BSG). There has been considerable progress in management strategies affecting all aspects of clinical care since the publication of previous BSG guidelines in 2004, necessitating the present revision. Key components of the present document worthy of attention as having been subject to re-assessment, and revision, and having direct impact on practice include: The data generated by the nationwide audits of inflammatory bowel disease (IBD) management in the UK in 2006, and 2008. The publication of 'Quality Care: service standards for the healthcare of people with IBD' in 2009. The introduction of the Montreal classification for Crohn's disease and ulcerative colitis. The revision of recommendations for the use of immunosuppressive therapy. The detailed analysis, guidelines and recommendations for the safe and appropriate use of biological therapies in Crohn's disease and ulcerative colitis. The reassessment of the role of surgery in disease management, with emphasis on the importance of multi-disciplinary decision-making in complex cases. The availablity of new data on the role of reconstructive surgery in ulcerative colitis. The cross-referencing to revised guidelines for colonoscopic surveillance, for the management of metabolic bone disease, and for the care of children with inflammatory bowel disease. Use of the BSG discussion forum available on the BSG website to enable ongoing feedback on the published document http://www.bsg.org.uk/forum (accessed Oct 2010). The present document is intended primarily for the use of clinicians in the United Kingdom, and serves to replace the previous BSG guidelines in IBD, while complementing recent consensus statements published by the European Crohn's and Colitis Organisation (ECCO) https://www.ecco-ibd.eu/index.php (accessed Oct 2010).